Color and surface gloss stability of bis-acryl and resin composite after exposure to cigarette smoke - Rocha, Rafael Santos; Ruano, Victor; Souza, Maurício Yugo; Salomão, Fabio Martins; Bresciani, Eduardo (Brazilian Dental Science, 2022)
Objective: To evaluate color and surface gloss stability of bis-acryl resins and resin composites, submitted to artificialstaining with cigarette smoke. Material and Methods: Specimens of each material were prepared (n=15). Two resincomposites (GrandioSO [RCG], Filtek Supreme [RCZ]) and five bis-acryl resins (Luxatemp Star [BisLUX], Protemp4[BisPRO], Structor3 [BisSTR], Visalys Temp [BisVIS] and Yprov [BisYPR]) were tested. Initial color was assessed using aspectrophotometer and surface gloss with a glossmeter. Samples were submitted to smoke exposure (10 cigarettes under8 minutes per cycle). After 3 and 6 cycles, color and gloss were reassessed. Final readings were performed after brushprophylaxis. Data were analyzed using two-way repeated ANOVA and Tukey’s test (p